Adding of apatinib and camrelizumab to overcome de novo trastuzumab resistance of HER2-positive gastric cancer: A case report and literature review - Huifang Lv; Yunduan He; Caiyun Nie; Feng Du; Xiaobing Chen (Frontiers Media S.A., 2023)
Background: Studies confirmed that trastuzumab plus fluorouracil-based chemotherapy improves the survival to more than 1 year in human with human epidermal growth factor receptor-2 (HER2)-positive advanced gastric cancer. However, there are still a small proportion of patients who do not benefit from trastuzumab treatment.Case summary: Here, we described a case report of de novo trastuzumab resistance in HER2-positive gastric cancer. Concomitant cyclin-E1 (CCNE1) and HER2 amplification are associated with de novo trastuzumab resistance. Genomic analysis demonstrated CCNE1 amplification and TP53 mutation in a HER2-positive gastric cancer patient. This patient achieved significant survival benefit and good safety when the patient received triple regimens consisting of trastuzumab, apatinib, and camrelizumab.Conclusion: Trastuzumab plus camrelizumab plus apatinib has the potential efficacy in HER2-positive gastric cancer patients who were previously treated with trastuzumab plus chemotherapy. This may lead to a new solution to trastuzumab resistance.